Lived religion in a digital age: Technology, affect and the pervasive space-times of “new” religious praxis - GAO, Quan (Institutional Knowledge at Singapore Management University, 2022)
This paper explores how Christian practices of prayer are being reconfigured through digital media in Singapore. Although digital technologies are an area of burgeoning interest amongst social and cultural geographers, the ways in which these technologies reconfigure the space-times of religious praxis and engender new affective relations or subjectivities of religion have not yet been embraced. This paper fills the lacuna by bringing existing studies on religion, technology and affect into constructive conversation with each other. By elaborating on digital prayer as an affective assemblage of religious practice, we show how digital technologies blur institutional boundaries and create new affordances for lived religious subjectivities beyond the ‘officially sacred’. Then, we consider how digital media may produce new atmospheres that shape the affective formation of religious subjects. We outline four dimensions of affect that constitute the digitally-mediated affective atmospheres, which structure how prayer is felt and performed. Altogether, this article contributes an understanding of ‘digital prayer’ as a form of religious practice that enables an integrative, if at times ambiguous and politically-charged, experience for connecting religious belief with the rhythms of everyday life.